Oxidative damage and exocrine dysfunction of ovine fetal pancreas are induced by maternal nutritional restriction - Yang Zi; Chi Ma; Yilin Yang; Liwei Zhao; Yingchun Liu; Feng Gao (Revista Brasileira de Zootecnia, 2023)
ABSTRACT This study investigated oxidative damage and exocrine dysfunction of fetal pancreas caused by maternal nutritional restriction. Eighteen ewes carrying singleton fetus were randomly divided into control group (CG, ad libitum, 0.67 MJ ME/BW0.75/d, n = 6), restricted group 1 (RG1, 0.33 MJ ME/BW0.75/d, n = 6), and restricted group 2 (RG2, 0.18 MJ ME/BW0.75/d, n = 6) at d 90 of pregnancy. Maternal undernutrition was imposed from d 90 to 140 of pregnancy. At 140 d of gestation, fetal blood and pancreas tissue were collected to determine fetal pancreatic extracellular matrix, antioxidant capacity, and indicators of exocrine dysfunction. With the decrease of maternal nutrition, the fetal body weight, pancreatic weight, and DNA content were reduced in RG2 compared with CG, and increased and thickened collagen fibers were observed in RG2. Fetuses in RG2 exhibited increased collagen 3 (COL3) and fibronectin (FN) levels relative to CG, and the COL1:COL3 ratio was lower than that of the CG. For RG1, we found increased COL3 compared with CG. Malondialdehyde, serum amylase, and serum lipase in fetal pancreas in RG2 increased, but the total antioxidant capacity (T-AOC) decreased compared with the CG. The impaired ovine fetal pancreas growth, antioxidant imbalance, and pancreatic exocrine dysfunction are induced by maternal undernutrition during late pregnancy.